Spain : Financial Sector Assessment Program-Technical Note-Determinants of Bank Profitability. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2017)
This Technical Note discusses the recommendations in the Financial Sector Assessment Program for Spain regarding determinants of bank profitability. Profitability remains higher for Spanish banks than for European peers, especially supported by relatively high net interest margins; however, some Spanish banks still have higher nonperforming loans (NPLs) and provision-to-asset ratios. Panel regression analysis suggests that Spanish banks' profitability is influenced by a combination of structural and cyclical factors, similar to those influencing other European banks and global systemically important banks. The IMF mission recommends further steps to reduce NPLs and legacy assets, continued cost-cutting measures to enhance the profitability of Spanish banks, and stronger communication between supervisors and banks on business models.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet